1987
DOI: 10.1088/0031-9155/32/5/007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro dielectric properties of human tissues at radiofrequencies

Abstract: In vitro permittivity measurements of excised human liver, spleen, kidney and cardiac muscle at frequencies from 10 kHz to 100 MHz are described. An end-of-the-line capacitive sensor and a computer-controlled network analyser HP 3577 were employed. The results were compared with human data reported by other investigators as well as with the animal (cat) data obtained earlier in this laboratory. It was found that the conductivity of most of the human tissues tested was significantly higher than that of the anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…In one of the most comprehensive studies, Gabriel et al (1996) reported the dielectric properties of a large number of biological tissues including freshly excised bovine and porcine tissue, human autopsy material, and human skin and tongue over a frequency range of 10 Hz-20 GHz. Dielectric data for various human and animal tissues reported in other studies (Foster et al 1979, Surowiec et al 1987, Peyman et al 2001, Schmid et al 2003, Lazebnik et al 2006, Abdilla et al 2013, Sasaki et al 2014 align with the data presented in (Gabriel et al 1996), which is widely used in electromagnetic modeling and assessment of specific absorption rate. Stuchly et al (1982) studied inter-species differences in dielectric properties of skeletal muscle, brain cortex, spleen, and liver tissue between 0.1 and 10 GHz, and reported a very small difference (within system uncertainty) between the same tissues of different species, which led researchers to believe that the data from animal studies can be generalized and used for human tissue modeling.…”
Section: Introductionsupporting
confidence: 76%
“…In one of the most comprehensive studies, Gabriel et al (1996) reported the dielectric properties of a large number of biological tissues including freshly excised bovine and porcine tissue, human autopsy material, and human skin and tongue over a frequency range of 10 Hz-20 GHz. Dielectric data for various human and animal tissues reported in other studies (Foster et al 1979, Surowiec et al 1987, Peyman et al 2001, Schmid et al 2003, Lazebnik et al 2006, Abdilla et al 2013, Sasaki et al 2014 align with the data presented in (Gabriel et al 1996), which is widely used in electromagnetic modeling and assessment of specific absorption rate. Stuchly et al (1982) studied inter-species differences in dielectric properties of skeletal muscle, brain cortex, spleen, and liver tissue between 0.1 and 10 GHz, and reported a very small difference (within system uncertainty) between the same tissues of different species, which led researchers to believe that the data from animal studies can be generalized and used for human tissue modeling.…”
Section: Introductionsupporting
confidence: 76%
“…Several previous studies have shown that tumor tissue has lower measured electrical resistivity than normal tissue in the radiofrequency range, and that this difference in resistivity becomes more pronounced at even lower frequencies ( Fig. 1 intro) [2][3][4][5]. A previous modeling study that utilized the frequency-dependent electrical resistivity values from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have investigated the electrical properties of different cancer tissues over a wide frequency range (from 1 kHz to 100 MHz) [2][3][4][5], and have found that the electrical resistivity of tumor tissue is significantly lower than normal tissue, with a more pronounced difference at lower frequencies. An example of this trend is shown graphically in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…If these waves are resonant, the result may be rapid heating [13][14][15][16]. Unfortunately, the conductors are often closely surrounded by tissue, whose dielectric constant is high at standard clinical frequencies (63.85 MHz for 1 H MRI at 1.5 T) [17], so the resonant length is short. Development of decoupling methods to control spurious resonances is more difficult for long conductors.…”
Section: Introductionmentioning
confidence: 99%